Clinical characteristics, comorbidities, and correlation with advanced lipedema stages: A retrospective study from a Swiss referral centre - Xhyljeta Luta; Giacomo Buso; Enrica Porceddu; Roxani Psychogyiou; Sanjiv Keller; Lucia Mazzolai (PLoS ONE, 2025)
Introduction Lipedema is a chronic condition involving abnormal fat deposition in the lower limbs, often underdiagnosed, and poorly understood. We examined the epidemiological and clinical characteristics of a large patient cohort in Switzerland and their associations with disease severity. Methods We included women aged 18 and over with lipedema at Lausanne University Hospital (CHUV), Switzerland. Demographic and clinical data, including disease type, stage, symptoms, and comorbidities, were collected. Descriptive statistics were used to summarise the data, and logistic regression was employed for analysis. Results A total of 381 females (mean age 41.9 years) were included, mostly classified as type III (48.3%) and IV (30.2%) lipedema. In our population, 26.6% of patients were classified as stage 1, 44.5% as stage 2, and 28.9% as stages 3–4. Family history was reported in 49.9%, with symptoms often starting during adolescence (62.2%). Pain affected 87.9%, and quality of life (QoL) was significantly reduced, with 71.5% reporting low physical and 67.4% low mental well-being. Comorbidities were present in 92.1%, increasing with advanced disease stage, with chronic venous disease (86.2%) and obesity (51.7%) being the most common. Univariate analysis showed advanced lipedema was associated with age (OR: 1.07, 95% CI: 1.05–1.09), BMI (OR: 1.24, 95% CI: 1.19–1.29), and comorbidities (OR: 1.59, 95% CI: 1.39–1.81). Multivariate analysis confirmed age (OR: 1.06, 95% CI: 1.04–1.08) and BMI (OR: 1.22, 95% CI: 1.17–1.28) as correlates with disease stage. Conclusions Our study highlights frequent comorbidities in patients with lipedema, including chronic venous disease, obesity, and mental health conditions such as anxiety and depression. The distribution of comorbidities supports the need for tailored management. The correlation between disease stages, age, and BMI suggests potential progression, warranting confirmation through prospective studies.